The BMS Tool Monitoring Vertiv UPS and Vision Lithium-Ion Battery System - Sithole, Tshepo; Veerdhi, Vasudeva Rao; Sithebe, Thembelani (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2024)
In my previous work published in an acknowledged publication, titled